Aberrantly Expressed Galectin-9 Is Involved in the Immunopathogenesis of Anti-MDA5-Positive Dermatomyositis-Associated Interstitial Lung Disease - Liang, Lin; Zhang, Ya-Mei; Shen, Ya-Wen; Song, Ai-Ping; Li, Wen-Li; Ye, Li-Fang; Lu, Xin; Wang, Guo-Chun; Peng, Qing-Lin (Frontiers in Cell and Developmental Biology, 2021)
Background: Rapidly progressive interstitial lung disease (RP-ILD) has high mortality rate and poor prognosis. Galectin-9 (Gal-9) plays multiple functions in immune regulation. We investigated Gal-9 expression in dermatomyositis (DM) patients and its association with DM-ILD. Methods: A total of 154 idiopathic inflammatory myopathy patients and 30 healthy controls were enrolled in the study. Cross-sectional and longitudinal studies were used to analyze the association between serum Gal-9 levels and clinical features. Enzyme-linked immunosorbent assay and qRT-PCR were used to examine Gal-9 expression in the sera and isolated peripheral blood mononuclear cells (PBMCs) from DM patients. Immunohistochemistry was performed to analyze the expression of Gal-9 and its ligand (T-cell immunoglobulin mucin (Tim)-3 and CD44) in lung tissues from anti-melanoma differentiation-associated gene 5 (MDA5)-positive patients. The effect of Gal-9 on human lung fibroblasts (MRC-5) was investigated in vitro. Results: Serum Gal-9 levels were significantly higher in DM patients than in immune-mediated necrotizing myopathy patients and healthy controls (p < 0.001). Higher serum Gal-9 levels were observed in anti-MDA5-positive DM patients than in anti-MDA5-negative DM patient (33.8 (21.9–44.7) vs 16.2 (10.0–26.9) ng/mL, p < 0.001). Among the anti-MDA5-positive DM patients, serum Gal-9 levels were associated with ILD severity. Serum Gal-9 levels were significantly correlated with disease activity in anti-MDA5-positive DM patients in both cross-sectional and longitudinal studies. PBMCs isolated from anti-MDA5-positive DM patients (3.7 ± 2.3 ng/mL) produced higher levels of Gal-9 than those from immune-mediated necrotizing myopathy patients (1.1 ± 0.3 ng/mL, p = 0.022) and healthy controls (1.4 ± 1.2 ng/mL, p = 0.045). The mRNA levels of Gal-9 were positively correlated with levels of type-I interferon-inducible genes MX1 (r = 0.659, p = 0.020) and IFIH1 (r = 0.787, p = 0.002) in PBMCs from anti-MDA5-positive DM patients. Immunohistochemistry revealed increased Gal-9 and Tim-3 expression in the lung tissues of patients with DM and RP-ILD. In vitro stimulation with Gal-9 protein increased CCL2 mRNA expression in MRC-5 fibroblasts. Conclusions: Among anti-MDA5-positive DM patients, Gal-9 could be a promising biomarker for monitoring disease activity, particularly for RP-ILD severity. Aberrant expression of the Gal-9/Tim-3 axis may be involved in the immunopathogenesis of DM-ILD.